Increased treatment persistence and its determinants in women with osteoporosis with prior fracture compared to those without fracture. Issue 3 (March 2016) - Jacob, L.; Dreher, M.; Kostev, K.; Hadji, P.
Abstract Summary The purpose of this study is to analyze treatment persistence in patients with osteoporosis after fracture diagnosis in German primary care practices. We found that pain increased treatment persistence. One key next step is to demonstrate whether or not this pain is related to fracture. Introduction To analyze treatment persistence in patients with osteoporosis after fracture diagnosis in German primary care practices. Methods This study included postmenopausal women with osteoporosis aged between 40 and 90 years from 1188 general and 175 orthopedist practices in Germany. Treatment started between 2004 and 2013. The primary outcome measure was treatment persistence within 12 months after therapy initiation. Discontinuation of treatment was defined as a period of at least 90 days without therapy. Persistence analyses were carried out using Kaplan-Meier curves and log-rank tests, and the analyses of the impact of fracture on discontinuation risk were based on Cox regression models (with and without adjustment for pain medications). Results Thirteen thousand nine hundred seventy-five subjects (mean age = 74.8 years) were included in the group with fracture before therapy initiation and 18, 138 (mean age = 72.7 years) in the group without fracture. Within 12 months after treatment initiation, therapy persistence increased with the delay between osteoporosis diagnosis and therapy initiation, rising from 40.7 % when the delay was lower than or equal to 12 months to 44.3 % when it exceeded 36 months (p value <0.0001). Fracture only decreased the risk of treatment discontinuation when the model was not adjusted for pain medications (HR = 0.95, 95 % CI 0.93–0.98, p value <0.0001). Conclusions Pain increased treatment persistence in women with osteoporosis and fracture. Further studies are needed to better understand factors influencing persistence.